A Summary of NCSER-Funded Projects in the Area of Transition Outcomes for Secondary Students With Disabilities. (September 2018) - Test, David W.; Terrell, Misty; Clark, Kelly A.; Rusher, Dana E.
Special education practitioners are required to use instructional practices based on scientific research. Conducting high-quality research can be expensive and researchers often need federal funding to assist in documenting effective practices. The National Center for Special Education Research (NCSER) within the Institute of Education Sciences (IES) is a preferred source of funding for this type of special education research. The purpose of this review was to summarize publications from grants funded from 2006 until 2013 by NCSER in the area of Transition Outcomes for Special Education Secondary Students, describe major findings, and discuss their contributions to the field. We reviewed information from 22 grants and 132 articles published in refereed journals with an additional one article in press. Contributions to the field, limitations, suggestions for future research, implications for practice, and conclusions are discussed.